The Ethic Values of 13-to 16-year-old Lithuanian Adolescents - Šaulienė, Valdonė (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryAs stated by the science of educology, at the tage of adolescence, education can make the greatest impact on the formation of a personality and the contextualization of one’s own value. The article deals with the 13-to 16-year-old adolescents’ perception of national values and its expression in the context of modern Lithuanianness. The research instrument – an essay – helps to determine younger teens’ national values, analysis of young people’s experience of values, feelings, and attitudes. The context of modern Lithuanianness is understood as a totality of cultural values created by the nation, handed on from generation to generation via education and the regularly updated cultural whole – the common language, common past and destiny, national mentality, traditions, landscape – by the patriotic love of homeland, its preservation and survival point of view. The scientific problem of research is formulating by questions: what are the moral values of Lithuanians aged 13 to 16 years and what factors affect the formation of national self-value in modern Lithuania? The aim of the research was to reveal the values of a young man as the representative of the nation, on the basis his its own national concept of culture. The analysis of the scientific literature found that the adoration of national values in modern state is giving way to civic, often formal, commitment to the nation. However, it is a theoretical assumption that the citizenship, its political base being composed of human rights and freedoms, is able to create an environment that patriotism would become a quiet and of course human and civil status by internalising the spiritual primer. An empirical analysis of the data has revealed that external factors militate young people unpatrioticly: distrust of government decisions, problems of economics and emigration, countrymens’ selfish behaviour. On the other hand, young people express very mature thoughts about the value of human life in the homeland. Patriotic love is characterized by emotions, personal experience with romantic elements. It may be that the feeling of love is the missing conection between knowing and acting in the interests of the homeland. But pragmatism is already rooted in adolescents. young people are often pondering whether it is worth to be attached to the endangered national values; they understand that more benefits are affered to a person by owning than by being. When the spirituality of a nation goes down the collective idealism disappears.Key words: adolescence, national values, modern Lithuanianness, self-value.